Analysis of the prognostic value of thyroglobulin antibody change trends during follow-up after 131I treatment in patients with differentiated thyroid carcinoma - Ge, Hua; Chen, Wenxin; Lin, Zhiyi; Li, Yuxuan; Chen, Shuting (Frontiers in Oncology, 2025)
ObjectivesThe prognostic value of thyroglobulin antibody (TgAb) and its trends during follow-up periods may guide the treatment plans in patients with differentiated thyroid cancer (DTC) following surgery, however, there is still a lack of sufficient data. This study aims to evaluate the impact of change trends in TgAb levels on the prognosis of patients with DTC and to explore its potential application in clinical practice.Materials and methodsA retrospective analysis was conducted on the medical records of 2,981 DTC patients who underwent surgery followed by 131I treatment. Among these, 248 patients with positive TgAb before treatment and had a follow-up period at least 12 months were included. Patients were categorized into four subgroups based on changes in TgAb levels: the Negative Conversion Group (TgAb shifted from positive to sustained negativity), the Decrease Group (TgAb decreased by more than 50% but remained positive), the Stable Group (TgAb fluctuated by ≤ 50% throughout follow-up), and the Increase Group (TgAb increased by 50% or more). Clinical and histopathological data among the four groups, as well as disease persistence/recurrence status after 131I treatment, were compared.ResultsPre-treatment TgAb levels in the Negative Conversion Group were significantly lower than those in the other three groups (P<0.001). Compared to the Negative Conversion Group, the Stable Group had more postoperative lymph node metastases (P<0.05). Although pre-treatment TgAb levels in the Increase Group were lower than those in the Decrease Group, the Increase Group required significantly more treatments and a higher total dose of 131I (P<0.05). Analysis of the relationship between TgAb trends and treatment outcomes revealed 34 cases of recurrent/persistent DTC. The Negative Conversion Group had significantly better outcomes than the Stable Group and Increase Group (P<0.001, P=0.007), while the Decrease Group showed better outcomes than the Stable Group (P=0.045).ConclusionsNegative conversion or a decrease in TgAb levels was associated with a favorable prognosis, whereas stable or increased TgAb levels indicated a higher risk of persistent/recurrent DTC. For patients with positive TgAb serum levels, monitoring the TgAb trend changes during follow-up should be a clinical priority, with timely adjustments to individualized treatment plans.